INTEGRAL EDUCATION, TIME AND SPACE: PROBLEMATIZING CONCEPTS - Ana Elisa Spaolonzi Queiroz Assis; Celso Mendes Ferreira da Silva (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
Integral Education, despite being the subject of public policy agenda for some decades, still carries disparities related to its concept. In this sense, this article aims to problematize not only the concepts of integral education but also the categories time and space contained in the magazines Em Aberto. They were organized and published by the National Institute of Educational Studies Anísio Teixeira (INEP), numbers 80 (2009) and 88 (2012), respectively entitled "Educação Integral e tempo integral" and " Políticas de educação integral em jornada ampliada". The methodology is based on Bardin's content analysis, respecting the steps of pre-analysis (research corpus formed by the texts in the journals); material exploration (reading the texts encoding data choosing the registration units for categorization); and processing and interpretation of results, based on Saviani's Historical-Critical Pedagogy. The work reveals convergent and divergent conceptual multiplicity, provoking a discussion about a critical conception of integral education. Keywords: Integral Education. Historical-Critical Pedagogy. Content Analysis.